Oral Bioavailability and Plasma Disposition of Pefloxacin in Healthy Broiler Chickens - Martínez, María-Aránzazu; Ares, Irma; Rodríguez, José-Luis; Martínez, Marta; Martínez-Larrañaga, María-Rosa; Isea, Gerardo; Anadón, Arturo (Frontiers in Veterinary Science, 2017)
The pharmacokinetics of pefloxacin after single 10 mg/kg BW intravenous (IV) and oral doses were studied in healthy broiler chickens. For 24 h, serial blood samples were obtained after IV and oral administration. Concentrations of pefloxacin and its major metabolite N-demethyl pefloxacin (norfloxacin) were measured by use of high-performance liquid chromatography. The plasma concentrations–time data were found to fit a two-compartment open model. For pefloxacin, the elimination half-life (t½β) was 8.44 ± 0.48 and 13.18 ± 0.82 h after IV and oral administration, respectively. After single oral dose, pefloxacin was rapidly absorbed with an absorption half-life (t½a) and TMAX of 0.87 ± 0.07 and 2.01 ± 0.12 h, respectively. Maximum plasma concentration (CMAX) was 4.02 ± 0.31 µg/mL. Oral bioavailability of pefloxacin was found to be 70 ± 2%. Pefloxacin was converted to N-demethyl pefloxacin (norfloxacin). This metabolite represented 5% of the parent drug plasma concentrations. The maximal plasma concentration (CMAX) of N-demethyl pefloxacin (norfloxacin) was calculated as 0.19 ± 0.01 mg/mL. The t½β of N-demethyl pefloxacin after oral pefloxacin administration was 10.93 ± 0.80 h. The results indicate that an oral dose of 10 mg pefloxacin/kg BW, every 24 h, should be effective in treatment of the most systemic infections in poultry.